2016
DOI: 10.1017/s1742058x15000181
|View full text |Cite
|
Sign up to set email alerts
|

Intersectional Presentations

Abstract: In recent decades the number of women and minorities elected to public office has increased significantly, prompting a wealth of studies examining the ways these different gender and racial identities shape elected officials’ appeals to constituents. However, much previous research focuses on representational differences among either men and women or Anglos and minorities, neglecting the intersection of race and gender. We seek to fill this void by examining differences in presentation styles among Latina and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Generally, WOC differ from their white male and female counterparts in the way they position themselves as candidates. According to Brown & Gershon (2016b), minority women discuss gender and race more than their counterparts. Minority women also discuss issues that affect WOC and other groups more broadly than their white counterparts.…”
Section: Woc Representation and Consciousnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, WOC differ from their white male and female counterparts in the way they position themselves as candidates. According to Brown & Gershon (2016b), minority women discuss gender and race more than their counterparts. Minority women also discuss issues that affect WOC and other groups more broadly than their white counterparts.…”
Section: Woc Representation and Consciousnessmentioning
confidence: 99%
“…Minority women also discuss issues that affect WOC and other groups more broadly than their white counterparts. Black women, in particular, are more likely to discuss these issues rather than their own coethnic and gendered group (Brown & Gershon 2016b, 98–99, 101–102). Theoretically, black women are expected to be the most inclusive when evaluating their support for WOC candidates.…”
Section: Woc Representation and Consciousnessmentioning
confidence: 99%
“…Our findings have implications for the quality of representation. For example, the use of communal traits on websites might be a type of symbolic representation (Brown and Gershon 2016;Mansbridge 1999;Pitkin 1967), showing that traits stereotypically associated with women are valued in the political sphere. And, to the extent that certain strategies enhance women's electoral prospects, there will be implications for increased descriptive representation in government.…”
Section: Discussionmentioning
confidence: 99%
“…Further, an advantage to coding websites is that every candidate has one, while not every candidate runs political advertisements. Several scholars use websites to capture various types of campaign content, including issue emphasis for men and women running for office (Dolan 2005(Dolan , 2008(Dolan , 2014bEvans and Clark 2016;Herrick 2016;Kahn 1993;Lee and Lim 2016;Niven and Zilber 2001;Schneider 2014b); trait emphasis for men and women candidates (Bauer 2020b;Fridkin and Kenney 2014;Schneider 2014b); the impact of mixed-gender races compared to single-gender races on campaign appeals (Dolan 2005(Dolan , 2008Schneider 2014b); and mentions of gendered and racial identities (Brown and Gershon 2016).…”
Section: The Use Of Stereotypic and Counterstereotypic Strategies On ...mentioning
confidence: 99%
“…Cargile (2016) found that while minority voters generally view Latinas as competent on feminine issues, white voters see Latinas as less favorable on feminine traits and policy issues compared to their white counterparts. This latter perspective translates into the idea of a double disadvantage that disproportionately affects minority female candidates (Brown and Gershon 2016). Not only are Latinas significantly disadvantaged from being women, but are also “multiply burdened” by the combination of their intersecting identities (Crenshaw 1989: 140).…”
Section: Intersectional Identities and Attitudes Toward Latinasmentioning
confidence: 99%